Pengembangan Bahan Ajar Pembelajaran Membaca Pemahaman Literal Berbasis Literasi Kitab Kuning Mahasiswa Program Studi PBSI STKIP Nurul Huda Sukaraja - Suryani, Suryani; Retno Kuspiyah, Hastuti; Fitriyah, Lailatul (GERAM: Gerakan Aktif Menulis, 2020)
To follow up on previous research and improve reading comprehension by developing literacy-based teaching materials for the yellow book were the reason for conducting this research. The research objective was to produce teaching materials learning products in the form of student worksheets for literal reading comprehension based on yellow book literacy in the PBSI STKIP Nurul Huda Sukaraja study program. This research was a kind of development research. The method used was the model development method. The population was all students of the PBSI study program first semester, with 15 students as a sample. The approach used was a mixed-method—data collection techniques in observation, interviews, questionnaires, and tests. The analysis technique that used was qualitative and quantitative data. The analysis findings showed that the teaching materials were in the form of student worksheets, which have special characters proven to help students learn literal reading comprehension material. Furthermore, based on quantitative analysis, it was found that the t-test of sig. (2 tailed) = 0.043 ≤ 0.05.